A Comparative Analysis of the Socioeconomic Dimensions of LGBTI Exclusion in Serbia - World Bank (Washington, DC, 2022)
The primary objective of this research was to provide Serbian policy makers, civil society, and development partners with evidence of the socioeconomic status of lesbian, gay, bisexual, transgender, and intersex (LGBTI) people in Serbia. The findings of the report, which were derived from a survey of LGBTI people, help to address the significant quantitative data gap on the lives of LGBTI people in Serbia and seek to inform policies and programs to address LGBTI exclusion. The survey was designed to collect and document evidence of the socioeconomic status of LGBTI people in Serbia rather than to explore policy or programming responses. However, the findings revealed that, going forward, certain areas warrant further investigation and greater attention from a policymaking perspective. These include: expanding the LGBTI evidence base; increasing LGBTI diversity in public sector employment; improving trust in government and institutions; and bolstering awareness and capacity to effectively address transgender issues. In addition to the above, the objective of the research was to test a survey methodology that addresses the persistent challenge of generating data that allow robust comparisons between the lives of LGBTI people and the general population. Such comparative data provide more valuable evidence about the unique challenges faced by LGBTI people by framing these challenges within the context of the experiences of the general population. The methodology and statistical analysis used here also offer a technique for other researchers interested in understanding the experience of LGBTI people compared to the population at large. The report presents the results of the survey and, where appropriate, attempts to contextualize the findings. However, where there is insufficient data and information to analyze and provide this contextualization, the report simply presents the results of the survey and does not attempt to explain the differences observed. Going forward, it would be beneficial to collect more data that allow in-depth analyses of the differences observed between LGBTI people and the general population.